2021
DOI: 10.1001/jamapsychiatry.2020.2902
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Prenatal Cannabis Exposure and Childhood Outcomes

Abstract: In light of increasing cannabis use among pregnant women, the US Surgeon General recently issued an advisory against the use of marijuana during pregnancy.OBJECTIVE To evaluate whether cannabis use during pregnancy is associated with adverse outcomes among offspring. DESIGN, SETTING, AND PARTICIPANTSIn this cross-sectional study, data were obtained from the baseline session of the ongoing longitudinal Adolescent Brain and Cognitive Development Study, which recruited 11 875 children aged 9 to 11 years, as well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(171 citation statements)
references
References 73 publications
(99 reference statements)
8
146
1
Order By: Relevance
“…Current-clamp recordings were made with electrodes filled with a solution containing the following (in mM): 144 KCl, 10 HEPES buffer, 3.45 BAPTA, 1 CaCl 2 , 2.5 Mg 2 ATP and 0.25 Mg 2 GTP, pH 7.2–7.4, 275–285 mOsm. As previously described 1,11 , this solution had no effect on the holding current of the dopamine cells. Current-clamp experiments were performed in the absence of any pharmacological blocker, that is, in regular ACSF.…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Current-clamp recordings were made with electrodes filled with a solution containing the following (in mM): 144 KCl, 10 HEPES buffer, 3.45 BAPTA, 1 CaCl 2 , 2.5 Mg 2 ATP and 0.25 Mg 2 GTP, pH 7.2–7.4, 275–285 mOsm. As previously described 1,11 , this solution had no effect on the holding current of the dopamine cells. Current-clamp experiments were performed in the absence of any pharmacological blocker, that is, in regular ACSF.…”
Section: Methodssupporting
confidence: 62%
“…Children with a parent who has a mental illness or substance use disorder have a higher risk of psychiatric problems themselves 4,5 . Critically, prenatal cannabis exposure (PCE) increases the risk for child psychopathology, ranging from affective symptoms to ADHD and psychotic-like experiences 611 . With recreational cannabis legalization and permissive sociocultural attitudes expanding worldwide, and the use of cannabis among pregnant women on a sharp rise 1214 , concern increases over the long-term negative impact on next generation health (i.e., pediatric concern) 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have indicated that cannabis use leads to FGR and postnatal neurodevelopmental outcomes, however they are confounded by sociodemographic factors and the fact that users often used other drugs (e.g., tobacco) ( 18 , 19 , 23 , 24 ). Indeed, more contemporary studies, some of which account for multiple factors, including in utero exposure to other drugs (tobacco, alcohol, benzodiazepine, and opioids), race, age, medical insurance, parity, and marital status, report that prenatal cannabis exposure alone is sufficiently predictive of LBW, PTD, and NICU admission ( 25 29 ).…”
Section: Physiological Outcomes Of Prenatal Cannabinoid Exposurementioning
confidence: 99%
“…Indeed, in a more recent retrospective observational cohort, a positive maternal Δ9–THC urine test at the first prenatal visit was associated with abnormal 12-month developmental scores in infants, as measured by the Ages and Stages: Social–Emotional Questionnaire (ASQ-SE) ( 27 ). Moreover, recent cross-sectional results from the ongoing Adolescent Brain Cognitive Development (ABCD) study, which recruited 11,875 children aged 9–11 years, found that prenatal exposure to cannabis was associated with deficits in attention, thought, and social problems after accounting for potentially confounding covariates ( 29 ). A moderate increase in the incidence of intellectual disability and learning disorders was also observed in a large retrospective analysis of children born between 2007 and 2012 in Ontario, Canada, though these results were not statistically robust ( 85 ).…”
Section: Neurodevelopmental Outcomes Of Prenatal Cannabinoid Exposurementioning
confidence: 99%
“…Paul et al explored the impact of prenatal cannabis exposure on childhood outcomes, taking data from the cross-sectional adolescent brain and cognitive development study of over 11 000 children aged 9-11 and their caregivers. 4 The issue is highly relevant given that US data show a greater than 100% rise in past-month cannabis use in women between 2002 and 2017, and there is evidence that Δ-9-tetrahydrocannabinol (THC) crosses the placenta, interfacing with the fetal endocannabinoid system that is involved in brain development. In the era of cannabis-derived medicinal products, there have also been debates on using cannabis for nausea in pregnancy.…”
mentioning
confidence: 99%